Sosisalisasi dan Peningkatan Kapasitas Masyarakat Dalam Penyusunan Rencana Kelola dan Konservasi Hutan Mangrove Desa Buruk Bakul Kecamatan Bukit Batu, Bengkalis - Yusni Ikhwan Siregar; Defri Yoza; Efriyeldi Efriyeldi (CANANG: Jurnal Pengabdian Masyarakat, 2022)
Scientists concern on environmental services of the tropical ecosystem increase in the last decade. As a part of blue ecosystem, mangrove forest plays an important role from prespective of ecological, physical and social concern. Scientists suggest that the ecosystem could enrole in mitigation and resilience of climate change. In contrary, degradation and land conversion rate of the ecosystem is alarming all over the world including in Bengkalis Regency. Therefore attempts to overcome the problem become important. Local people as a main stakeholder need to be aware of environmental service of mangrove in their own region. The objective of the study was to increase perception, capacity and participation local people on conservation efforts. During the extention the local participants were introduced with the practical knowledge and skill in that of small scale mangrove ecoturism business.The participants of total 35 persons, with background of farmer, fishermen, local leader, young leader, and of non-government organization “Sekat Bakau” of the Buruk Bakul were trained on ecological, economical and social benefit of mangrove ecosystem. Further, materials on sustainability of ecoturism principles based on ecological, social and economical benefit to the environment and society, were discussed in classroom. Inherently, ecoturism could empower people through microscale business, educate as people well as enhance participation of local people. The effectiveness of the extention were greatly well based on evaluation to the participants and showed a significant result in perception, participation. Apparently, the level of capacity and knowledge on ecoturism were categorized into very good (60%), good (30%) and fair (10%). Based on that, the extention were categorized success.